2022
DOI: 10.51599/are.2022.08.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Economic coping strategies and food security in poor rural households

Abstract: Purpose. This study aims to analyze economic coping strategies and their relationship to the food security of poor rural households. Methodology / approach. This research was conducted by comparing food crop farming households with those who farm plantation crops. The used data were sourced from surveys in four sample rural areas in two districts of Jambi Province, Indonesia, namely Merangin Regency and Tanjung Jabung Timur Regency. The used analysis tool was Structural Equation Modeling (SEM). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(31 reference statements)
1
1
0
1
Order By: Relevance
“…This proportion, associated with the dominance of employment in the agricultural sector, indicates that income from employment in the agricultural sector is deemed insufficient to meet the needs of the second generation. The results of this study are consistent with previous findings (Junaidi et al, 2022), which suggest that rural communities' strategy for increasing incomes is to find side jobs.…”
supporting
confidence: 92%
“…This proportion, associated with the dominance of employment in the agricultural sector, indicates that income from employment in the agricultural sector is deemed insufficient to meet the needs of the second generation. The results of this study are consistent with previous findings (Junaidi et al, 2022), which suggest that rural communities' strategy for increasing incomes is to find side jobs.…”
supporting
confidence: 92%
“…Research by Praza & Shamadiyah (2020) in North Aceh, Devi et al (2020) in Ciamis, Yuliana et al (2013) in Bandar Lampung, and Sukandar (2007) in Banjar have identified socioeconomic factors affecting food security, including age, education, head of household's occupation, household knowledge, family size, asset ownership, household income, and location. Junaidi et al (2022) observed differences in food security between plantation and food crop households, where family characteristics and coping strategies influenced food security in plantation households, but not in food crop households. Furthermore, Junaidi et al (2020) found that economic coping strategies and social capital significantly influence food security among poor urban households in Jambi Province.…”
Section: Introductionmentioning
confidence: 84%
“…Families with many household members can divide duties among each other in production or agricultural activities. In return, they can increase the food produced for consumption and surplus, which can generate income; hence, households consume a more diversified diet and increase their food availability [43].…”
Section: Discussionmentioning
confidence: 99%